Preimplantation genetic diagnosis: achievements and limitations - Sepúlveda, Soledad (2014)
Preimplantation genetic diagnosis (PGD) is the study of chromosomal or genetic alterations in the human embryo before transfer to the mother. It determines those embryos free of chromosomal abnormalities or genetic mutations. This review describes the 5-year experience including 711 cycles of an assisted reproduction center in Peru, performing PGD to embryos on day 3 of development. Preimplantation genetic diagnosis would be an effective tool to select embryos with higher implantation potential, which may lead to a healthy live birth.